The reality of the educational role of the secondary school in the educational region of Hail in achieving the social goals of sustainable development from the point of view of its teachers - Alzabanii, Nawadir Murbih; Alhadif, Najla' Muhamad (Journal of Educational and Psychological Sciences, 2023)
The study aimed to identify the reality of the educational role of the secondary school in the educational region of Hail in achieving the social goals of sustainable development from the point of view of its teachers, and to identify its obstacles and come up with proposals to try to overcome them, and the study identified these goals, which are (the eradication of poverty, good health, and quality education The study followed the descriptive survey method, and the questionnaire was applied as a study tool on secondary school teachers in the Hail region in the Kingdom of Saudi Arabia, and the sample consisted of (317) teachers who were chosen randomly. The responses of the study sample related to the reality of the educational role of the secondary school in the educational region of Hail in achieving the social goals of sustainable development from the point of view of its teachers was (3.94) and a standard deviation (0.92), and the highest ranked phrases were (the school works to activate the Islamic values that urge on social solidarity) with an arithmetic mean (4.28) and a standard deviation (0.75), and the general average of the responses of the study sample related to the obstacles of the educational role of the secondary school b The Hail Educational District in achieving the social goals of sustainable development from the point of view of its teachers was (3,64), which represents a high degree of obstacles, and a standard deviation (1). This result may be attributed to the fact that with the awareness of the role of secondary school in achieving sustainable development goals; However, there are still many obstacles that require more work to overcome. In order to complete the role of the secondary school in this aspect.
Keywords: The role of the secondary school; sustainable development; Hail region